Obesity: Obvious Obstacle; Oblivious To Opportunity - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Obesity has been known to human kind for thousands of years. Descriptions of obesity are visible in ancient art and sculpture, and can be read in texts and manuscripts of yesteryear.1 It is in recent decades, however, that thecondition has emerged as a pandemic. Figures from the World Obesity Federation suggest that nearly 3.3 billion adults across the globe will live with overweight and obesity by the year 2035, as compared to 2.2 billion in 2020. Apart from these, 770 million children andadolescents (aged 5 to 19 years) will live with overweightand obesity in 2035, an increase from 430 million in 2020.2This reflects an increase from 42% of adults in 2020 toover 54% by 2035, and from 22% to over 39% childrenand adolescents over the same time frame.